DNA polymerase delta-dependent repair of DNA single strand breaks containing 3'-end proximal lesions. - Parsons, J; Preston, B; O'Connor, T; Dianov, G (2007)
Base excision repair (BER) is the major pathway for the repair of simple, non-bulky lesions in DNA that is initiated by a damage-specific DNA glycosylase. Several human DNA glycosylases exist that efficiently excise numerous types of lesions, although the close proximity of a single strand break (SSB) to a DNA adduct can have a profound effect on both BER and SSB repair. We recently reported that DNA lesions located as a second nucleotide 5'-upstream to a DNA SSB are resistant to DNA glycosylase activity and this study further examines the processing of these 'complex' lesions. We first demonstrated that the damaged base should be excised before SSB repair can occur, since it impaired processing of the SSB by the BER enzymes, DNA ligase IIIalpha and DNA polymerase beta. Using human whole cell extracts, we next isolated the major activity against DNA lesions located as a second nucleotide 5'-upstream to a DNA SSB and identified it as DNA polymerase delta (Pol delta). Using recombinant protein we confirmed that the 3'-5'-exonuclease activity of Pol delta can efficiently remove these DNA lesions. Furthermore, we demonstrated that mouse embryonic fibroblasts, deficient in the exonuclease activity of Pol delta are partially deficient in the repair of these 'complex' lesions, demonstrating the importance of Pol delta during the repair of DNA lesions in close proximity to a DNA SSB, typical of those induced by ionizing radiation.